(untitled) (Bangladesh Pharmaceutical Journal, 2022)
Rheumatoid arthritis (RA) is one of the most commonly occurring autoimmune disorders in both men and women. Management of RA is posing challenge to the modern medicine practice. Non-management of RA is associated with both articular and extrarticular complications. Currently, immuno-modulators and immune-suppressants are the mainstay of therapy. However their use is limited due to severe consequences. Present systematic review is carried out to identify potential herbs and herbal preparations claimed to have anti-arthritis properties. Findings of our study shows that leaves, barks and root parts of the plants are the most commonly associated to have anti-rheumatism effect. Most of the plants studies belongs to lamiaceae, leguminosae, malastomataceae, cobretaceae and apocynaceae families. These plant preparations commonly producing their effect through inhibition of IL-1, IL-6, IL- 1ß, cytokines and cyclooxygenase. The effect is also mediated through TNF-α, ROS, NF-ΚB, prostaglandin and leukotriene. Based on these results we recommend that there are some promising number of plants and plant preparations which may be explored further to find out a novel and effective therapy for RA having unique mechanism of action. These may be used as adjunct therapies or nutritional supplements in the treatment of arthritis. Bangladesh Pharmaceutical Journal 25(2): 125-136, 2022 (July)